Violent accounts : understanding the psychology of perpetrators through South Africa's Truth and Reconciliation Commission - Kraft, Robert Nathaniel (New York University Press, 2014)
Violent Accounts presents a compelling study of how ordinary people commit extraordinary acts of violence and how perpetrators and victims manage in the aftermath. Grounded in extensive, qualitative analysis of perpetrator testimony, the volume reveals the individual experiences of perpetrators as well as general patterns of influence that lead to collective violence. Drawing on public testimony from the amnesty hearings of the South African Truth and Reconciliation Commission, the book interweaves hundreds of hours of testimony from seventy-four violent perpetrators in apartheid South Africa, including twelve major cases that involved direct interactions between victims and perpetrators. The analysis of perpetrator testimony covers all tiers on the hierarchy of organized violence, from executives who translated political doctrine into general strategies, to managers who translated these general strategies into specific plans, to the staff--the foot soldiers--who carried out the destructive plans of these managers.
Keywords: South Africa. -- Truth and Reconciliation Commission.; South Africa. -- Truth and Reconciliation Commission; Restorative justice -- South Africa -- Psychological aspects.; Violence -- South Africa -- Psychological aspects.; Apartheid -- South Africa -- Psychological aspects.; Justice réparatrice -- Afrique du Sud -- Aspect psychologique.; Violence -- Afrique du Sud -- Aspect psychologique.; Apartheid -- Afrique du Sud -- Aspect psychologique.; HISTORY -- Africa -- South -- General.; HISTORY -- Africa -- South -- Republic of South Africa.; PSYCHOLOGY -- General.; Apartheid -- Psychological aspects; Violence -- Psychological aspects; South Africa